Y = 5x2 + 7x - 3
use the pq-formula: x2 + px + q
p = 7
q = -3
x = -p/2 +- sqrt( (p/2)2 - q)
x = -7/2 +- sqrt ( (7/2)2 -(-3))
x = -3,5 +- sqrt ((49/4) + 3)
x = -3,5 +- sqrt (12,25 + 3)
x1 = -3,5 + sqrt(15,25)
x2 = -3,5 - sqrt (15,25)
X= (3/5 , -2)
The answer to the math problem -3 7x plus 7 is x equals 1/3.
3+3x+7x=13 3x+7x=10 10x=10 x=1
Subtract by 7x and divide by 2.
7x+7=28x 28x-7x=7 21x=7 x=3
X= (3/5 , -2)
True.
-7x - 2y = -3
The answer to the math problem -3 7x plus 7 is x equals 1/3.
3+3x+7x=13 3x+7x=10 10x=10 x=1
Subtract by 7x and divide by 2.
4x+9 = 7x+3 4x-7x = 3-9 -3x = -6 x = 2
7x + y + 3 = y7x + 3 = 07x = -3x = -3/7
7x + 8 = 11x + 3, solve for xsubtract 7x from both sides8 = 11x - 7x + 38 = 5x + 3subtract 3 from both sides5 = 5xdivide both sides by 51 = x.
7x+7=28x 28x-7x=7 21x=7 x=3
X = -3
Why not? The statement is trivially true, meaning it holds for all values of x.